Pengembangan Telehealth â€œSIPISPeKaâ€ sebagai Solusi Mensukseskan Program Indonesia Sehat dengan Pendekatan Keluarga (PIS-PK) - Aliyanto, Warjidin; Suarni, Lisa; Sono, Sono; Hajar, Alex Iskandar (Politeknik Kesehatan Tanjung Karang, 2021)
There is a phenomenon in Indonesia that shows that the use of telehealth is not optimal in hypertension management in Indonesian health services which has an impact on cost efficiency both for the government and patients in the community. Based on this, researchers are interested in researching the use of telehealth in PISPK-based homecare services in health services in Indonesia. The purpose of this study was to assess the quality of Telehealth Applications in the Program Indonesia Sehat Pendekatan Keluarga (PISPK). The research design was the development of a telehealth prototype named SIPISPeKa which was by the needs of the Community Health centers in providing health services for families in the category of troubled families in the PISPK assessment. Research respondents are families with the unhealthy category in the Healthy Family Index in Tanjung Aman Village, Kotabumi Selatan District was 147 respondents. Processing and data analysis in this study using univariate analysis using frequency distribution. SIPISPeKa as a telehealth/telehealth media is declared worthy of being assessed from 4 aspects of assessment, namely: telehealth media principles, governance, web-based communication media, and relevance to the PISPK program. Assessors' comments and suggestions for SIPISPeKa include the need to improve the SIPISPeKa application to make it friendlier, easier to use and more able to replace the presence of health workers in families with low IKS scores.